2020
DOI: 10.2337/figshare.13235543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dapagliflozin and the Incidence of Type 2 Diabetes in Patients With Heart Failure and Reduced Ejection Fraction: An Exploratory Analysis From DAPA-HF

Abstract: <b>Objective </b> <p>The SGLT2 inhibitor dapagliflozin reduced the risk of cardiovascular mortality and worsening heart failure in the <a>Dapagliflozin and Prevention of Adverse-Outcomes in Heart Failure </a>trial (DAPA-HF). This report explores the effect of dapagliflozin on incident type 2 diabetes in the non-diabetic cohort enrolled in the trial.</p> <p><b> </b></p&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Importantly, the benefits of SGLT2i for HF were documented to be similar in patients with or without DM 45,46 . On the other hand, in HF and reduced ejection fraction, treatment with dapagliflozin can reduce the incidence of new DM and subsequent mortality 47 . These results are compelling and suggest the need for further assessment of the effects of SGLT2i on the progression of HF associated with prediabetes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly, the benefits of SGLT2i for HF were documented to be similar in patients with or without DM 45,46 . On the other hand, in HF and reduced ejection fraction, treatment with dapagliflozin can reduce the incidence of new DM and subsequent mortality 47 . These results are compelling and suggest the need for further assessment of the effects of SGLT2i on the progression of HF associated with prediabetes.…”
Section: Discussionmentioning
confidence: 98%
“…45,46 On the other hand, in HF and reduced ejection fraction, treatment with dapagliflozin can reduce the incidence of new DM and subsequent mortality. 47 These results are compelling and suggest the need for further assessment of the effects of SGLT2i on the progression of HF associated with prediabetes. The ongoing DANish randomized, double-blind, placebo-controlled trial in patients with chronic HEART failure (DANHEART) will provide important messages on the potential benefit and safety of metformin in patients with HF and with prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Furthermore, a secondary analysis of the Dapagliflozin in Patients with Heart Failure and Reduced Ejection Fraction (DAPA-HF) trial showed that dapagliflozin lowered the incidence of diabetes in patients with HF and reduced ejection fraction. 30 In addition to SGLT2i, catheter ablation emerged as another important prevention strategy for cardiovascular death and HHF in patients with AF. Catheter ablation was associated with significantly lower rates of HHF and death Diabetes, heart failure, and NT-proBNP in atrial fibrillation 2373 in patients with HF and an LVEF ≤35%.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate a complementary value of dapagliflozin in addition to the established combined therapy for HF and Worsening HF episodes (either unplanned hospitalization or urgent heart failure visit requiring intravenous therapy but not requiring a hospital admission) or CV death, analyzed as time to first event either in the full population or in patients with LVEF \ 60% further evidence for its use in ambulatory patients with HFrEF to improve clinical outcomes [25]. Finally, an exploratory analysis on the effect of dapagliflozin on incident T2D in the cohort without diabetes enrolled in the trial showed that treatment with dapagliflozin reduced the incidence of new diabetes [26] and therefore could be exerting a protective effect in these patients with HF where the risk of developing diabetes is elevated.…”
Section: Mechanism Effectmentioning
confidence: 99%